Qualitative Assessment of Quality and Readability of Patient-Directed Arabic Online Resources for Cochlear Implants in Children - Saad A. Sanad; Aseel M. Mokhtar; Manar O. Alharbi; Hisham B. Alem; Afnan F. Bukhari; Faisal Zawawi (International Archives of Otorhinolaryngology)
Objective To assess the readability and quality of various websites providing information on cochlear implantation (CI) in children in Arabic.